Studies of suspension droplet evaporation on soft substrates for stretchable electronics applications - Saengchairat, Nitipon (Nanyang Technological University, 2020)
Evaporation of sessile drops is a common phenomenon in various problems, but its fundamental understanding remains modestly unknown. Despite numerous reports of the factors affecting the evaporation processes, the effect of substrate elastic modulus has been seldom reported. This work aims to experimentally investigate the dependence of substrate elastic modulus or Young modulus on the evaporation dynamics of the sessile liquid drops containing the dispersed microparticles and the resulting deposition patterns. In this work, the evaporation dynamics of the sessile ethanol drops was experimentally investigated using thermographic approach. As a result, the substrate Young modulus can control the evaporation dynamics and the radius of deposition patterns. The temperature distribution across the liquid-vapour interface deviates larger on the substrate with higher Young modulus. Moreover, the evaporation dynamics of water droplets containing non-spherical particles such as carbon nanotubes were analysed as a function of substrate temperature and particle concentration. The evaporation dynamics and the resulting deposition patterns are comparable to that of the spherical microparticles. In addition, the conductive patterns were directly printed on the surface of substrates with varying Young modulus. The properties of the printed patterns dependent of the substrate Young modulus were measured. It was demonstrated that the substrate with lower Young modulus could prevent the formation of sintered particles due to the leaching of residual polymers, therefore, suppressing their electrical conductivity. To conclude, the substrate Young modulus can notably control the evaporation dynamics and the properties of printed patterns.